Adaptive Optimization and Planning Design Method for DC Distribution Grid System Based on Optical Storage Direct and Flexible Constructed Cluster - Chenghui Lin; Zhanpeng Xu; Qihui Feng; Wuliang Chen; Jianyang Zhu (IEEE Access)
The topology design of DC distribution networks has a natural advantage in accommodating distributed DC power sources such as photovoltaic (PV) and energy storage systems, which is one of the effective ways to achieve carbon peaking and carbon neutrality goals. However, random power fluctuations of distributed PV can cause serious problems in DC distribution networks, such as bi-directional power flow variations, frequent node voltage violations and increased network losses. To address these challenges in the design of a DC distribution network integrating distributed PV and energy storage, this paper proposes a coordinated optimal design approach that simultaneously considers voltage regulation and network loss optimization. An adaptive coordinated optimization design scheme featuring adaptive switching between voltage correction and network loss optimization modes is proposed. The design scheme achieves coordinated control of the voltage source converter (VSC), DC/DC converter and controllable energy storage resources, balancing the requirements of system loss reduction and voltage safety control. It also provides guidance for the planning and design of future PV-storage DC distribution network systems based on flexible DC technology.